2021
DOI: 10.1038/s41573-021-00233-1
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting oxidative stress in disease: promise and limitations of antioxidant therapy

Abstract: Oxidative stress is a component of many diseases, including atherosclerosis, chronic obstructive pulmonary disease, Alzheimer disease and cancer. Although numerous small molecules evaluated as antioxidants have exhibited therapeutic potential in preclinical studies, clinical trial results have been disappointing. A greater understanding of the mechanisms through which antioxidants act and where and when they are effective may provide a rational approach that leads to greater pharmacological success. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
1,021
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,581 publications
(1,041 citation statements)
references
References 291 publications
(295 reference statements)
8
1,021
1
11
Order By: Relevance
“…Prior studies have shown that endothelial dysfunction acts in the preclinical development of atherosclerosis, and inflammation could increase the vulnerability of plaques. Under oxidative stress, LDL could be transformed into oxidized low-density lipoprotein (ox-LDL), and vascular endothelial dysfunction and increased permeability could promote the deposition of ox-LDL in the intima (33). Furthermore, the accumulated ox-LDL contributes to the initiation of inflammatory reactions, infiltration of monocytes and T cells, and accumulation of extracellular matrix (34).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that endothelial dysfunction acts in the preclinical development of atherosclerosis, and inflammation could increase the vulnerability of plaques. Under oxidative stress, LDL could be transformed into oxidized low-density lipoprotein (ox-LDL), and vascular endothelial dysfunction and increased permeability could promote the deposition of ox-LDL in the intima (33). Furthermore, the accumulated ox-LDL contributes to the initiation of inflammatory reactions, infiltration of monocytes and T cells, and accumulation of extracellular matrix (34).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induced by excessive ROS accumulation causes severe damage to cellular lipids, DNA, and proteins, linked to cancers, inflammatory, cardiovascular, and neurological diseases [ 33 , 34 , 35 ]. LPS activation of macrophages results in the formation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Developing multiparametric state and process speci c redox signatures could have far-reaching signi cance. For example, disease speci c redox state signatures could rapidly screen how large numbers of patients respond to a treatment; which might make it easier to evaluate the therapeutic value of next-generation antioxidants 38 .…”
Section: Discussionmentioning
confidence: 99%